The optimal currency distribution of a central bank's foreign exchange reserves - Kaija-Leena Rikkonen (Bank of Finland, 1989)
The purpose of this study is to establish a currency distribution for foreign exchange reserves of a central that would minimize the risks related to the increased exchange rate volatility. The study also addresses issues, such as the preservation of value of reserves, the numeraire currency, and the central bank's attitude towards risk. The portfolio chöice problem is solved through the mean-variance framework of expected returns. The uncertainty under consideration is sole1y due to exchange rate changes in case of nomina1 returns, and additionally due to changes i n the defl ator i n case of real returns, because the reserves are assumed to be invested in one-month Eurocurrency deposits. Three alternative expectations hypotheses of the exchange ra te behavior, namely (i) Random Wa1k, (ii) Open Interest Parity and (iii) modified interest parity (a1lowing for the existence of a risk premium) are employed for isolating the unexpected component of the exchange rate changes.
URN:NBN:fi:bof-201807301774
Keywords: 330